Characterisation of the NAC's p(66)/Be(40) neutron therapy beam in terms of primary and scattered dose components - Schreuder, A. N (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Med.)) -- University of Stellenbosch, 1992.